Beyond Forensic Evidence: Examining Sexual Assault Medical Forensic Exam Mechanisms that Influence Sexual Assault Case Outcomes. Issue 7 (April 2022) - Tiry, Emily; Zweig, Janine; Walsh, Kelly; Farrell, Lauren; Yu, Lilly
Despite the widespread use of sexual assault medical forensic exams (SAMFEs), practitioners and researchers continue to debate the role of SAMFEs and the evidence they provide in the investigation and prosecution of sexual assault cases. Using data from a review of sexual assault cases reported to police between 2015 and 2017 in two jurisdictions ( n = 534), we use logistic regression examine whether the presence of a SAMFE predicts the likelihood of achieving criminal case processing outcomes and whether the relationship of the SAMFE with criminal case processing outcomes is moderated by other legal and extralegal case characteristics. We did not find evidence that the presence of a SAMFE in a case significantly predicts whether a suspect will be identified, arrested, or convicted overall, but we did find evidence of the SAMFE's injury documentation value for arrest. Researchers and practitioners should account for the multiple ways SAMFEs can influence decision-making in future research and policymaking.